Association Between Skin and Aortic Vascular Inflammation in Patients With Psoriasis: A Case-Cohort Study Using Positron Emission Tomography/Computed Tomography - Dey, Amit K. (JAMA Cardiol, 2017)
IMPORTANCE: Inflammation is critical in the development of atherosclerosis. Psoriasis is a chronic inflammatory skin disease that is associated with increased vascular inflammation by (18)fluorodeoxyglucose positron emission tomography/computed tomography in vivo and future cardiovascular events. It provides a human model to understand the effect of treating inflammation in a target organ (eg, the skin) on vascular diseases. OBJECTIVE: To investigate the association between change in skin disease severity and change in vascular inflammation at 1 year and to characterize the impact of 1 year of anti–tumor necrosis factor therapy on vascular inflammation. DESIGN, SETTING, AND PARTICIPANTS: In this prospective cohort study, 220 participants from outpatient practices were recruited at the US National Institutes of Health. A total of 115 consecutively recruited patients with psoriasis were followed up at 1 year. The study was conducted from January 1, 2013, through October 31, 2016, with data analyzed in November 2016. EXPOSURE: Skin inflammation measured as Psoriasis Area and Severity Index (PASI) score. MAIN OUTCOMES AND MEASURES: Vascular inflammation assessed as target-to-background ratio by (18)fluorodeoxyglucose positron emission tomography/computed tomography. RESULTS: Among the 115 patients, the mean (SD) age at 1-year follow-up was 50.8 (12.8) years and 68 were men (59%). The cohort had a low cardiovascular risk by Framingham risk score and mild-to-moderate psoriasis, with a median PASI score of 5.2 (interquartile range, 3.0-8.9). At follow-up, the total cohort had a median improvement in PASI score of 33%, with use of topical therapy (60%), biological therapy (66%, mostly anti–tumor necrosis factor) and phototherapy (15%) (P < .001). Moreover, improvement in PASI score was associated with improvement in target-to-background ratio of 6%, mainly driven by those with higher responses in PASI score (P < .001). This association persisted beyond traditional risk factors (β = 0.19; 95% CI, 0.012-0.375; P = .03) and was the strongest in those initiated with anti–tumor necrosis factor therapy (β = 0.79; 95% CI, 0.269-1.311; P = .03). CONCLUSIONS AND RELEVANCE: Improvement in psoriasis skin disease severity was associated with improvement in aortic vascular inflammation by (18)fluorodeoxyglucose positron emission tomography/computed tomography, with greater improvement in aortic vascular inflammation observed in those who had higher than 75% reduction in skin disease severity. These findings suggest that controlling remote target organ inflammation (eg, in the skin) may improve vascular diseases; however, randomized clinical trials are needed to confirm these findings.